Fugitive Truth: Renewing the Public Sphere in the Age of Post-Truth - Newman, Saul (Javnost-The Public, 2024)
In the sixty years since the publication of Jürgen Habermas' magnum opus, The Structural Transformation of the Public Sphere, the public sphere now faces a new threat in the era of “post-truth” politics. The preponderance of lies, mis/disinformation, “fake news”, “alternative facts”, conspiracy theories, and the general breakdown of trust in established sources of knowledge and information has led to the fragmentation and deepening polarisation of the public sphere - a situation deliberately promoted by right wing populist forces intent on fighting the “culture wars”. At the same time, the political space is being disrupted, in a different way, through new social movements and radical activism particularly around issues of climate change, inequality, racial injustice, and police violence. My aim is to show how these contemporary forms of dissent are engendering a new “structural” transformation of the public sphere. They create autonomous and critical spaces of collective engagement that call into question the legitimacy of dominant power structures. Understanding this process requires an alternative rendering of the relationship between truth and politics - something I develop through Michel Foucault's rethinking of the critical impulse of the Kantian Enlightenment and his later work on parrhesia.